Characterization of OFDR distributed optical fiber for crack monitoring considering fiber-coating interfacial slip. (January 2023) - Zhao, Lizhi; Tang, Fujian; Li, Hong-Nan; Ansari, Farhad
An analytical crack-strain transfer model considering interfacial bond-slip between optical fiber and fiber coating is proposed and experimentally validated for crack monitoring of structures. Interfacial shear stress-slip relationship between the optical fiber and fiber coating was determined by using pull-out tests, and a simplified trilinear three-stage interfacial shear stress-slip model was proposed. The model is incorporated into the development of a crack-strain transfer model between the structural substrate and the optical fiber, and the fiber strain distribution is analytically obtained and compared with the strain distribution as perfect bond is assumed between the fiber and fiber coating. Experiments were also conducted to validate the crack-strain transfer model by continuously monitoring corrosion-induced concrete cracking with OFDR distributed optical fiber. Compared with strain transfer models proposed by other researchers in the literature and perfect bond model, the crack-strain transfer model considering interfacial shear stress-slip mechanism between fiber and fiber coating agrees well with experimental results, especially for large crack monitoring.